Microstructure driven design of porous electrodes for molten carbonate fuel cell application: Recent progress. (25th September 2020) - Wejrzanowski, T.; Cwieka, K.; Skibinski, J.; Lysik, A.; Ibrahim, S. Haj; Milewski, J.; Xing, W.; Lee, C.-G.
Abstract: This paper presents progress in development of microstructure in MCFC electrodes. Within these studies the influence of microstructure parameters of materials, such as porosity and pore size distribution on the fuel cell power density is analyzed using pure nickel. The results indicate that the optimal range of porosity for MCFC electrodes can be related with specific surface area, which reveals maximum for volume fraction of pores being 55–60%. The porosity of the cathode should be 5–10% higher due to in situ oxidation taking place during the startup procedure. Pore size distribution, PSD, was found to be especially important in MCFC, where liquid electrolyte infiltrates electrodes by capillary action. Through the application of specific porogens, multimodal PSD can be obtained, which significantly enhances reference cell power density. Optimization of basic microstructure parameters informed the design of a new concept MCFC cathode incorporating bi-layered materials, where each layer is appointed a different role. The application of commercial nickel foam as the gas side layer of the cathode increased power density and reduced the brittleness of the element, which is of key importance from the technological point of view. Highlights: The results of MCFC electrodes microstructure optimization were demonstrated. Multimodal distribution of pore size was proven to be beneficial for MCFC electrodes. Design of new, layered concept of MCFC cathode was presented; Application of foam-supported cathodes increase power density and reduce brittleness.